(untitled) (African Journal of Biomedical Research, 2022)
Evolvulus alsinoides Linn. is a small perennial herb that belongs to the family convolvulaceae. It is used as adaptogenic, antihypertensive, antiphlogistic, antipyretic, antiseptic, aphrodisiac, and in the management of neurodegenerative disorders. The effect of the aqeous extract was investigated on some blood parameters and spleen histology in rats. Fifty young adult male Wistar rats were divided into five groups of ten rats each. Group I served as the control group; groups II and III were administered with 150 mgkg-1 and 250 mgkg-1 respectively. Groups IV and V were administered with 350 mgkg-1 each. The plant extract was administered by gavage for 28 days. Blood parameters were evaluated manually. The extract contained carbohydrate, cardiac glycosides, flavonoids, saponins, tannins, and terpenoids. Sections from spleen administered with 350 mgkg-1 revealed prominent germinal centers with expanded lymphoid cells. Significant increases in red blood cell (p<0.001) and white blood cell (p<0.001) counts were observed. These suggest that the plant has haematinic and immunostimulatory effects. These are important properties that can be of benefit medicinally. However, further research on the safety levels of oral consumption of Evolvulus alsinoides Linn. is recommended.